MODIFICATION OF TAM MODEL TO ANALYZE CONSUMER BEHAVIOR IN USING QRIS - Hasyim, Fuad; Wahyudi, Agung; Setiawan, Agus (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
Digital technology has rapidly developed in recent years, affecting the culture and patterns of transactions. One of the innovations in digital payments is the emergence of the Quick Response Indonesian Standard (QRIS). However, massive QRIS education at all levels of society is not in line with the community's response, which still maintains traditional payment patterns, especially in the Soloraya area. This study aimed to analyze the factors influencing the adoption of QRIS (technology use). This approach was carried out using technology acceptance model modification theory. A sample of 100 people was obtained using a simple random sampling method in communities located in the former Surakarta (Soloraya) residency, namely Sragen, Sukoharjo, Karanganyar, Wonogiri, Klaten, Boyolali and Surakarta City Regencies. Data analysis techniques with partial least squares structural equation Modelling (PLS-SEM). The results show that all variables in the TAM modification construct consisting of perceived usefulness, perceived ease of use, perceived risk and perceived security influence the decision to use QRIS with intention as a mediating variable.